Profile of male Brazilian injecting drug users who have sex with men - Ferreira Aline Dayrell; Caiaffa Waleska Teixeira; Bastos Francisco I.; Mingoti Sueli Aparecida (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
This study aims to characterize the profile of male injecting drug users who have sex with other men (MSM IDUs) recruited through a cross-sectional multi-city survey (AjUDE-Brasil II Project) in six Brazilian cities, in 2000-2001. MSM IDUs were compared to other male IDUs using bivariate and multivariate procedures (logistic regression and answer tree analysis with the CHAID algorithm). Among the 709 male IDUs, 187 (26.4%) reported ever having had sex with other men, while only 37 reported sex with other men in the previous six months. MSM IDUs were more likely to be unemployed (OR = 2.3), to have injected tranquilizers (OR = 3.6), and to be HIV-seropositive (OR = 2.1), compared to other male IDUs. Male same-sex relations in this subgroup appear to be associated with strategies to finance drug consuming habits, including sex for drugs with occasional female partners or obtaining injection paraphernalia from occasional sex partners. Further studies should focus on this especially vulnerable subgroup of IDUs, due to the bidirectional and complex interrelationships between their drug injecting habits and sexual risk behaviors.